Development of E-Modules Assisted By Qr Code Through PBL Learning Based on Socio Scientific Issues (SSI) to Improve Critical Thinking Skills: Review Article - Maharani, Richa Nan; Widarti, Hayuni Retno; Rokhim, Deni Ainur (Universitas Negeri Yogyakarta, 2025)
Problem-based learning based on Socio Scientific Issues (SSI) is teaching by solving a problem that is related to real world life, especially in raising issues or problems. This review article aims to analyse the research trend of e-module teaching materials through problem-based learning based on Socio Scientific Issues (SSI) in terms of its essence, advantages and disadvantages. The method used is a qualitative method of literature review study approach. The results of data analysis show that during the period 2018-2023, problem-based learning based on Socio Scientific Issues (SSI) which integrates social issues or problems in real life can help students develop critical thinking skills according to the level of contextual issues presented through teaching materials in the form of E-modules or electronic modules.